Successful management of cloud computing and DevOps - Jarvis, Alka; Prakash, Anand; Jose, Johnson (Quality Press, 2022)
"The decision to move to cloud revolves around technology, process, and total cost of ownership. A lack of knowledge often translates to direct loss of time and resources to a company. This book serves as an end-to-end decision-making guide for cloud transformation by offering a comprehensive view of the cloud ecosystem and the associated technology infrastructures. The focus of this book is not about a specific cloud provider, but rather about the underlying technologies that make cloud what it is today"--